Unfiltered : conflicts over tobacco policy and public health - Feldman, Eric A.; Bayer, Ronald (Harvard University Press, 2004)
"Unfiltered tells the story of how anti-smoking advocates, public health professionals, bureaucrats, and tobacco corporations have clashed over smoking regulation. The nations discussed in this book - Australia, Canada, Denmark, France, Germany, Japan, the United Kingdom, and the United States - restrict tobacco advertising, tax tobacco products, and limit where smoking is permitted. Each is also struggling to shape a tobacco policy that ensures corporate accountability, protects individual liberty, and asserts the state's public health power."--Jacket.